Chronic Pain - Marcus, Dawn (Springer, 2017)
Patients with chronic pain present a unique set of challenges to the primary care clinician. In Chronic Pain: A Primary Care Guide to Practical Management, Second Edition, leading pain specialist Dawn A. Marcus, MD, again offers practical, clear, and succinct evidence-based approaches to the diagnosis and treatment of the myriad painful conditions clinicians see in their offices every day, such as headache, back pain, arthritis, fibromyalgia, and abdominal pain. Sections addressing pain management in children, pregnant women, and seniors are also included. This new edition is designed to provide a pragmatic approach to assessing and treating the complex issues and characteristics of chronic pain patients (...)